Treatment Algorithms for Patients with Metastatic Non-Small Cell, Non-Squamous Lung Cancer - Melosky, Barbara (Frontiers in Oncology, 2014)
A number of developments have altered the treatment paradigm for metastatic non-small cell, non-squamous lung cancer. These include increasing knowledge of molecular signal pathways, as well as the outcomes of several large-scale trials. As a result, treatments are becoming more efficacious and more personalized, and are changing the management and prognosis of NSCLC patients, resulting in increased survival in select patient groups. In this paper a simplified algorithm for treating patients with metastatic non-small cell, non-squamous lung cancer is presented.